RESOLUSI KONFLIK BERLATAR AGAMA: STUDI KASUS AHMADIYAH DI KUDUS (Harmoni, 2013)
The purpose of this research are knowing the life of the Ahmadi community member in the city of Kudus, Central Java which can live together in peace with moslem people there; exploring conflict resolution model done by the Ahmadi community member in the city of Kudus, Central Java. The main source of the data of this research are observation and indepth interviews. The research methode used in this study was qualitative research methods. The results show that the Ahmadi community member in the city of Kudus did the conflict resolution so well in encountering conflict. These are: distributing flyers to residents of Colo, Kudus in 2006. Words written on flyers is ΓÇ£the same God, the same Prophet; in their mosque written ΓÇ£Laailahaillallah Muhammdurrasulullahilla; they embedded in social activities with the resident of non - Ahmadis in Colo; they are proactive and adhere to the the regulation and social norms which prevailing in their communites and living together with the all the Colo residents.
Keywords: Ahmadist; Kudus; no conflict; conflict resolution; Ahmadiyah; konflik